2019
DOI: 10.4103/nmj.nmj_34_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of thyroid disorders among patients attending University of Nigeria Teaching Hospital, Enugu, Southeastern Nigeria

Abstract: Introduction: Thyroid disorders (TDs) remain the second-most common endocrine disease after diabetes worldwide. Recently, there has been increased interest in the prevalence and pattern of TD based on the fact that it accelerates cardiovascular complications. However, there are limited data on the prevalence and pattern of TDs in the University of Nigeria Teaching Hospital (UNTH) Enugu, Southeast Nigeria. Objectives: We studied prevalence and pattern of TDs as seen in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
6
6
0
Order By: Relevance
“…This study also showed that the presence of hyperthyroidism was 21.97% and the percentage of hypothyroidism was 15.4%. These results are similar to the study in Nigeria which showed hyperthyroidism at 58%, hypothyroidism at 39% and euthyroid sick syndrome at 3.9 [12]. Similar to the study in the United States, 4.6% of the population had hypothyroidism (0.3% overt and 4.3% subclinical) and 1.3% had hyperthyroidism (0.5% overt and 0.7% subclinical) [13].…”
Section: Distribution Of Patients According To the Type Of Thyroid Dy...supporting
confidence: 89%
“…This study also showed that the presence of hyperthyroidism was 21.97% and the percentage of hypothyroidism was 15.4%. These results are similar to the study in Nigeria which showed hyperthyroidism at 58%, hypothyroidism at 39% and euthyroid sick syndrome at 3.9 [12]. Similar to the study in the United States, 4.6% of the population had hypothyroidism (0.3% overt and 4.3% subclinical) and 1.3% had hyperthyroidism (0.5% overt and 0.7% subclinical) [13].…”
Section: Distribution Of Patients According To the Type Of Thyroid Dy...supporting
confidence: 89%
“…The persistent significant proteinuria was 5.8% 15 in another community study. It was observed that Okafor et al 40 highlighting the enormity of diabetic nephropathy in Enugu, documented that the prevalence of albuminuria was 61.2%. This is alarming compared to 30% in United Kingdom while Mexican American was 31% 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-carcinogenic health concerns are more prevalent in children than in adults. Wang et al (2012) and Okafor et al (2019) uncovered that thyriod disorders (TDs) contribute to the total deaths in Nigeria.…”
Section: Discussionmentioning
confidence: 99%